APLIKASI GOOGLE MAPS API SISTEM INFORMASI PARIWISATA SUMATERA BARAT BERBASIS WEB - Ricat Ricat (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
This website is used to help tourists find tourist destinations and car rentals. To create a website program using Hypertext Preprocessor (PHP). For database use PhpMyAdmin. The method used is the Unified Modeling Language (UML) method. Based on testing that has been done using BLACBOX, UAT and questionnaires. The results of this website make it easy for tourists to travel with maps that can go directly to tourist sites and make it easier for tourists to understand what facilities are in place.